DEVELOPMENT OF CONSTRUCTION ACTIVITIES: LEGAL INNOVATIONS AND CHALLENGES OF TODAY - TYTOK, Viktoriya; EMELIANOVA, Olena; PYLYPCHUK, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes legal innovations and current challenges in the development of construction activities in Ukraine, in particular in the context of war and the country’s recovery from military trials. The article examines the impact of new legislative initiatives on the regulation of the construction sector, in particular, on improving administrative procedures, simplifying investment mechanisms, and integrating digital technologies into construction processes. The author emphasizes the need for legal changes to improve the efficiency and transparency of construction activities, which contributes to the development of the industry even in difficult wartime conditions. The article analyzes changes in legislation aimed at regulating construction, restoring destroyed facilities and optimizing land relations. Legal innovations in the field of construction activities regarding the update of estimate norms are considered. Updating the methods for calculating construction costs and applying resource element cost estimates contribute to the accuracy of financial planning and optimization of construction costs, in particular for facilities damaged as a result of hostilities. Regulations that ensure transparency of cost estimates are important, as well as changes in legislation on the management of construction waste that arises during the aftermath of destruction. The article emphasizes the importance of strategic decisions in the construction sector, which should not only facilitate the rapid restoration of infrastructure but also ensure sustainable development in the future. Changes in legislation should take into account the specifics of the ever-changing context, including current economic and environmental requirements. It is noted that legal innovations in construction activities not only facilitate the process of recovery in times of war, but also contribute to the creation of the basis for sustainable development of the industry in the future, improving its efficiency and adaptation to new realities. It is noted that the adopted legal initiatives form the basis for the sustainable development of the construction sector, which will contribute to the restoration of infrastructure and economic stability of the country.